Sustainable poultry production process to mitigate socio-economic challenge - Shamsuddoha, M.; Quaddus, Mohammed; Klass, D. (Emerald Group Publishing Ltd., 2015)
Purpose – The purpose of this paper is to review the literature and to develop a sustainable model for the poultry industry in an attempt to mitigate existing socio-economic problems. Sustainability along with positive socio-economic changes has gained prominence in recent years in academia and business in Bangladesh. This paper aimed at helping the poultry industry is used to develop a sustainable production process to mitigate socio-economical problems. Bangladesh poultry has yet to achieve sustainability in her extended forward and reverse supply chain. The design science method under a quantitative paradigm has been used in this study to develop a sustainable supply chain model for the case industry. A simulation model has been developed using the SIMUL8 software package to model the real poultry case. Finally, key performance indicators (KPIs) will be briefly discussed to illustrate the positive effects of developing a sustainable production process model. Design/methodology/approach – This study covers a literature review on environmental sustainability, reverse supply chain and Bangladesh poultry industry. This study adopted positivist ontology, empirical epistemology and quantitative methodology based on case studies of poultry industry. The design science methodology and case study method was chosen for this study. Design science is concerned with “devising artefacts to attain goals” (Simon, 1969). Design science is based on “build and evaluate” an artefact of a model (March and Smith, 1995). Here, an artefact means design and develop soft or hard objects that can meet specific purposes and goals (Venable, 2006a, 2006b). Case studies are observed descriptions of particular instance of an occurrence (Yin, 1994). Both primary and secondary information were used in this study. Findings – The findings of this study were mainly focused on developing a sustainable poultry model along with Islamic consensus. There is plethora research work conducted by the previous researcher. Such study will fill the research gap that also can guide to eliminate socio-economic problems of the society. Model output can easily determine the immediate impact over society, stakeholders and entrepreneurs. Optimality can be observed in the model environment so that real-life experiment does not require which is also expensive and time consuming. Research limitations/implications – The study only includes a sustainable poultry model with showing overall impact to mitigate the socio-economic problems in Bangladesh. This research can be extended more elaborately than this. Future research could be expanded based on different aspect of supply chain, Islamic finances and socio-economic problems. Practical implications – Poultry waste management could gain more social, economic and environmental benefit through implementing the model practically within the existing farm. Social implications – This paper provides a guidelines to create more employments and social benefits through sustainable poultry supply chain. Moreover, proper waste management can make it more worthy for the society. Originality/value – This paper has maintained originality to mitigate socio-economic challenge in Bangladesh through sustainable poultry supply chain.